Refinement and Scaling of Inclusive Agroecological Innovations for Livestock Management, Crop Rotations, and Soil Conservation in Semi-arid South Mediterranean Regions - Frija, Aymen; Idoudi, Zied; Rekik, Mourad; M'hamed, Hatem Cheikh; Bahri, Haithem; Ghedhoui, Slaheddine; Harrouchi, Faouzi; Rudiger, Udo (International Center for Agricultural Research in the Dry Areas, 2022)
The objective of this work is to i) present a socio-technical package of agroecological interventions that are already being tested for this type of mixed farming system in the semi-arid area of Tunisia, and ii) illustrate the scope and mechanisms for scaling up this package. Results further illustrate the key factors that have led to a change in attitude and behaviour among local actors and farmers towards a better co-generation, co-sharing, and adoption of agroecological principles at farm, community, and landscape levels. This work was presented at the Tropentag 2022 conference in Prague Czech University of Life Sciences, Prague/Czech Republic: September 14-16